Adjustable suture surgery for correction of various types of strabismus - (:unkn) unknown (SLACK INC, 2007)
BACKGROUND AND OBJECTIVE: This study was conducted to analyze the efficacy of the adjustable suture technique for correction of strabismus in patients with different types of strabismus. PATIENTS AND METHODS: This was an observational case series of patients who underwent the adjustable suture technique for correction of strabismus. A total of 33 adult patients (16 males and 17 females) with a minimum postoperative follow-up period of 6 months were included in the study. Patients were analyzed in three groups (patients with exotropia, esotropia, and vertical deviations). Success criteria determined were percentage change in the angle of deviation for far and near fixation, need for reoperation, and relief of diplopia. RESULTS: The median percentage change in the angle of deviation for far and near fixation was 86.60% and 84%, 92.50% and 94.44%, and 100% and 100% in the exotropia, esotropia, and vertical deviation groups, respectively. There was no need for reoperation, and postoperative adjustment performed 24 hours after surgery was needed in 30.3% of patients due to diplopia. a CONCLUSIONS: The adjustable suture technique seems to be an effective method in the correction of various types of strabismus.
Keywords: RECTUS MUSCLE; ANESTHESIA; RECESSION